Perlakuan Akuntansi Dana BOS (Studi Kasus Pada SD NU Hasyim Asy’ari Tahun 2020) - Richard Gerry; Ana Sopanah; Dwi Anggarani (BULLET : Jurnal Multidisiplin Ilmu, 2022)
−This study aims to determine the planning, implementation, ireporting, iand iaccountability iof ithe iBOS iFund ifor iSD iNU iHasyim iAsy'ari iin iMalang iCity iaccording ito ithe i2020 iBOS iTechnical iInstructions. iResearch isetting iat iSD iNU iHasyim iAsy'ari, iKotalama, iKedungkandang, iMalang iCity iwith i3 iinformants iThe isubjects istudied iwere ithe iPrincipal, ithe iSchool iTreasurer iand ithe iSchool iCommittee. iData icollection itechniques iusing iObservation, iInterview iand iDocumentation. iThe istages iof idata ianalysis itechniques iare idata icollection, idata ireduction, idata ipresentation iand iconclusion idrawing. iThe iresults iof ithis istudy iare i(1) iBOS iFund iPlanning iis iin iaccordance iwith ithe i2020 iBOS iTechnical iGuidelines iwhere ithere iis ia imutual iagreement iwith ithe ischool iin ithe ipreparation iof ithe iRKAS, i(2) iThe iimplementation iof ithe iuse iof iBOS iFunds iis iin iaccordance iwith ithe i2020 iBOS iTechnical iGuidelines iby icarrying iout iaccording ito ithe iplans ithat ihave ibeen imade. imade iin ithe iform iof iRKAS, i(3) iThe ifinancial ireporting iof iBOS iFunds iis iin iaccordance iwith ithe i2020 iBOS iTechnical iGuidelines iwith ithe icreation iof idocuments, i(4) ithe iFinancial iAccountability iof iBOS iFunds iis iin iaccordance iwith ithe i2020 iBOS iTechnical iGuidelines iis idocumented iin ithe iform iof ian iAccountability iReport.